“Science and Religion” Meets Popular Culture - Nairn, Anthony K. (Zygon, 2025)
The field of science and religion has grown significantly in recent decades, yet its insights remain largely disconnected from popular culture, where the conflict thesis persists. This article argues that popular culture is a primary vehicle for shaping public perceptions of science–religion interactions and therefore must be meaningfully integrated into scholarly analysis in the field of science and religion. This article, an introduction to science and religion for popular culture scholars, first outlines the complexity model, which challenges simplistic narratives by emphasizing historical and cultural contexts. It then examines the portrayal of science and religion in media, highlighting their reconfiguration within popular culture. Using Christopher Nolan’s Interstellar as a case study, the article demonstrates how the film employs theological motifs—such as the Holy Trinity, resurrection, and divine intervention—within a framework of hard science fiction. Interstellar exemplifies the complexity of science–religion engagement by bridging secular and spiritual narratives, underscoring the need for scholars to engage with media to reshape public understanding critically.